Single-Ion Magnetism in a Luminescent Er3+ β-Diketonato Complex with Multiple Relaxation Mechanisms - Martín-Ramos, Pablo; Ramos Silva, Manuela; Coutinho, Joana T.; Pereira, Laura C. J.; Chamorro-Posada, Pedro; Martín-Gil, Jesús (European journal of inorganic chemistry, 2014)
In the crystal structure of tris(2,2,6,6‐tetramethyl‐3,5‐heptanedionato)mono(bathophenanthroline)erbium(III), C57H73ErN2O6, the Er3+ ion is in an antiprismatic environment, surrounded by two N atoms and six O atoms. The β‐diketonato ligands show structural disorder. The ac susceptibility studies conducted at frequencies from 33 to 9995 Hz and at temperatures from 1.7 to 10 K revealed that the application of a static magnetic field induces a slow magnetic relaxation. Two relaxation modes (fast relaxation = FR; slow relaxation = SR) could be distinguished with energy barriers UFR/kB = 15.6 K and USR/kB = 22.4 K and relaxation times of 10–6 and 10–4 s, respectively. The Er3+ compound is luminescent in the solid state, emitting in the near IR region. A new Er3+ β‐diketonato compound is presented. In the presence of a variable magnetic field, this compound undergoes a dual relaxation process with distinct energy barriers and relaxation times. Furthermore, the compound absorbs radiation in the visible and UV region and emits in the near IR region.